An amazing alphabet - John Patience (New York : , Derrydale : Distributed by Crown Publishers, 1984)
Each letter of the alphabet is represented by a fantasy creature.
Keywords: Moncure, Jane Belk. -- Alphabet books. Alphabet books (Moncure, Jane Belk)